Exploring the Role of Media Use Within an Integrated Behavioral Model (IBM) Approach to Vote Likelihood. (March 2021) - Holbert, R. Lance; Dias, Nicholas C.; Hardy, Bruce W.; Jamieson, Kathleen Hall; Levendusky, Matthew S.; Renninger, Andrew S.; Romer, Daniel; Winneg, Kenneth M.; Pasek, Josh
Political interest is a key predictor of likelihood to vote. We argue that the political interest–vote intention relationship can be explained by well-established theories that predict behavior across domains (e.g., theory of reasoned action, theory of planned behavior). Relying on the integrated behavioral model, we propose a core mediation model with vote likelihood (i.e., behavioral intention) as the dependent variable. Two types of media use (conservative and liberal–moderate) are then assessed in relation to the core model. We explore the ways in which our results contribute to theory and outline a research agenda.